Size-Related Differences in the Thermoregulatory Habits of Free-Ranging Komodo Dragons - Henry J. Harlow; Deni Purwandana; Tim S. Jessop; John A. Phillips (International Journal of Zoology)
Thermoregulatory processes were compared among three-size groups of free-ranging Komodo dragons (Varanus komodoensis) comprising small (5–20 kg), medium (20–40 gm) and large (40–70 kg) lizards. While all size groups maintained a similar preferred body temperature of ≈35∘C, they achieved this end point differently. Small dragons appeared to engage in sun shuttling behavior more vigorously than large dragons as represented by their greater frequency of daily ambient temperature and light intensity changes as well as a greater activity and overall exposure to the sun. Large dragons were more sedentary and sun shuttled less. Further, they appear to rely to a greater extent on microhabitat selection and employed mouth gaping evaporative cooling to maintain their preferred operational temperature and prevent overheating. A potential ecological consequence of size-specific thermoregulatory habits for dragons is separation of foraging areas. In part, differences in thermoregulation could contribute to inducing shifts in predatory strategies from active foraging in small dragons to more sedentary sit-and-wait ambush predators in adults.